Comparative Analysis of Universal Newborn Hearing Screening Programs in Malaysia, China and Philippines (Journal of Governance and Development (JGD), 2023)
Universal Newborn Hearing Screening Program (UNHS) has developedrapidly and tremendously in the world, but developing countries needcontextual models for UNHS to optimize screening outcomes and costeffectiveness.Therefore, this study aims to document current UNHS practicesin three developing countries; Malaysia, Philippines and China with the aimof comparing the reported practices to bring about some recommendations.Based on the comprehensive review of reports, published research, and otherrelevant materials, it is found that UHNS practices in the selected countries(Philippine, Malaysia, and China) have commonalities and differences.Newborn hearing screening is made binding on all caregivers in Philippine,whereas it is just recommended in Malaysia and China. Nevertheless, theprotocols of UNHS program applied in the selected countries are similar. Inthe selected countries, the protocol involves OAE and AABR. Also, UNHShas been well instituted in the selected countries, but certain challenges(e.g. poor follow-up) are debilitating the effectiveness of the screening inthe selected countries, and the challenges should be well addressed andempirically studied. Furthermore, stakeholders could possibly benefit fromthe findings of this study and recognize the need to optimize the UNHSprogram through suggested factors. This study has hopefully contributedtowards the enrichment of the relevant literature, and it could serve as auseful guide for stakeholders with regards to improvement of UNHS programin their respective countries.